EFisiensi Biaya pada Badan Amil Zakat Nasional (BAZNAS) dalam Tinjauan Akuntabilitas Islam - Sandra Sukma Embuningtiyas; Mashudi Mashudi (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2020)
The purpose of this study is to measure the performance of the National Zakat Agency (BAZNAS) by using financial ratio analysis in this case cost efficiency in the Islamic accountability review. This research uses a combination of qualitative and quantitative methods. Data collection was carried out by means of documentation. The data analysis method used is an inductive and deductive frame of mind. Secondary data obtained through the baznas.go.id website regarding BAZNAS financial reports for the years 2012-2019. The results showed that the efficiency level of BAZNAS using the Operational Cost Ratio to Total Amil Rights obtained efficient results, then the efficiency level of BAZNAS using the Operational Cost to Total Collection ratio obtained efficient results, but the efficiency level of BAZNAS using the Ratio of Human Resources Costs to Total Collections resulted in inefficient. Suggestions for BAZNAS should pay more attention to the problem of cost efficiency in terms of Islamic accountability, namely accountability to Allah SWT, accountability to fellow humans, and accountability to nature.